ANTIMUTAGENIC ACTIVITY OF BINARA HERBS (ARTEMISIA VULGARIS L.) ETHANOL EXTRACT IN MALE MICE INDUCED BY CYCLOPHOSPHAMIDE - Meliala, Linta; Harahap, Urip; Harahap, Urip; Dalimunthe, Aminah; Dalimunthe, Aminah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: This study aims to evaluate the antimutagenic activity of binara herbs (Artemisia vulgaris L.) ethanol extract on male mice. Methods: Binara herbs powder was extracted is used ethanol 96% by maceration, then made into a suspension preparation used 0.5% carboxymethylcellulose with 3 dose variations (100, 200, and 300 mg/kg). Further, the extract was administrated orally in mice for 7 consecutive days. 4 h after the last orally, cyclophosphamide 50 mg/kg IP was injected. 30 h after cyclophosphamide injection, the animals were killed, and the samples of bone marrow were prepared and stained with gems. For each sample, 200 cells of polychromatic erythrocytes (PCE) and the same number of normochromatic erythrocytes (NCE) and the cells containing their micronucleus (MN) were counted using the MN test method in vivo. Results: Cyclophosphamide increased the frequency of MnPCE and decreased cell proliferation (PCE/PCE+NCE). All doses of extracts significantly reduced the frequency of MnPCE (p<0.05). The cell proliferation ratio (PCE/PCE+NCE) was also increased. The most effective dose is 300 mg/kg because it has the greatest ability to decrease the frequency of MnPCE and increase the cell proliferation ratio. Conclusion: Results of this study indicated that binara herbs (A. vulgaris L.) ethanol extract has potent antimutagenic activity.